2020
DOI: 10.1093/ajcn/nqaa096
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with vitamin D or ω-3 fatty acids in adolescent girls and young women with endometriosis (SAGE): a double-blind, randomized, placebo-controlled trial

Abstract: ABSTRACT Background Adolescents with endometriosis are a particularly underserved population who struggle with chronic pain. Despite widespread use, there are no published trials examining the individual effects of vitamin D and omega-3 (n–3) fatty acid supplementation on endometriosis-associated pain in adolescents. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 34 publications
1
70
0
5
Order By: Relevance
“…Results from trials in women with painful endometriosis have been less clear cut; in a pilot trial comparing women taking 1,000 mg O-PUFA with 1,000 mg olive oil for 8 weeks, there were no adverse effects but the study was underpowered for efficacy (Abokhrais et al, 2020). In a study focused on 147 young women (12-25 years of age) who were assigned to groups taking vitamin D, 1,000 mg O-PUFA, or placebo for 6 months, the change in pain scores was not statistically significant and there was improvement in the placebo group (Nodler et al, 2020). Further properly powered RCTs are required, and the impact of placebo on pain perception needs to be considered before we can be sure O-PUFA offers real clinical benefit.…”
Section: Novel Therapies For Endometriosis Based On Targeting Metabolic Endpointsmentioning
confidence: 99%
“…Results from trials in women with painful endometriosis have been less clear cut; in a pilot trial comparing women taking 1,000 mg O-PUFA with 1,000 mg olive oil for 8 weeks, there were no adverse effects but the study was underpowered for efficacy (Abokhrais et al, 2020). In a study focused on 147 young women (12-25 years of age) who were assigned to groups taking vitamin D, 1,000 mg O-PUFA, or placebo for 6 months, the change in pain scores was not statistically significant and there was improvement in the placebo group (Nodler et al, 2020). Further properly powered RCTs are required, and the impact of placebo on pain perception needs to be considered before we can be sure O-PUFA offers real clinical benefit.…”
Section: Novel Therapies For Endometriosis Based On Targeting Metabolic Endpointsmentioning
confidence: 99%
“…Thus, an anti-inflammatory diet could be useful. A prospective study has shown, for example, that the intake of fish oil (omega-3 unsaturated fatty acids) reduced the risk of EM recurrences [32]. The ratio of unsaturated fatty acids to saturated fatty acids was important in this context [32].…”
Section: Dietmentioning
confidence: 99%
“…A prospective study has shown, for example, that the intake of fish oil (omega-3 unsaturated fatty acids) reduced the risk of EM recurrences [32]. The ratio of unsaturated fatty acids to saturated fatty acids was important in this context [32]. Vitamin C, E and A, selenium and zinc also have an antioxidant effect.…”
Section: Dietmentioning
confidence: 99%
“…Researchers have also compared the efficacy of vitamin D and omega-3 fatty acids in reducing oxidative stress, pain, and the sizes of endometriotic lesions. In a randomized, double-blind, placebo-controlled study, female patients suffering from dysmenorrhea experienced a significant reduction in pain using the VAS score after taking vitamin D [ 129 , 130 ]. The participants in this study were randomly assigned to take either a placebo, 1000 mg fish oil, or 2000 IU vitamin D 3 [ 129 ].…”
Section: Treatments For Oxidative Stressmentioning
confidence: 99%